The social identity approach to understanding socio-political conflict in environmental and natural resources management. (September 2015) - Colvin, R.M.; Witt, G. Bradd; Lacey, Justine
Graphical abstract: Highlights: A conceptual model for ENRM conflict is presented. The social identity approach is used to understand subtleties of ENRM conflict. Conflict legacy: Interconnections between conflicts over time are important. Ways to alleviate conflict are identified by the social identity approach. Awareness of implications of social identity is important for ENRM. Abstract: Insights from the social identity approach can be useful in understanding the drivers of dysfunctional conflict in environmental and natural resources management (ENRM). Such conflicts tend to be shaped by multiple factors including: the governance arrangements that are in place and how deliberations are undertaken; the conduct and interactions of stakeholders and the wider citizenry; and the conflict legacy, which can perpetuate a 'culture of conflict' around particular issues. This paper presents an integrative conceptual model of the socio-political landscape of ENRM conflict, which draws these multiple factors together. The social identity approach is then introduced as an appropriate lens through which the drivers of conflict in ENRM can be further interrogated. Key social identity mechanisms are discussed along with their contribution to the proliferation of dysfunctional conflict in ENRM. Based on this analysis, it is found that the social identity approach presents a way to understand the subtle and sometimes invisible social structures which underlie ENRM, and that ENRM issues ought to be viewed as a series of conflict episodes connected across time and contexts by the conflict legacy. The conceptual model, and its interpretation through the social identity approach, raises a number of implications for the current theory, practice and institutions involved in the wicked socio-political landscape of ENRM. These implications are examined, followed by a discussion of some opportunities to address the impact of social identity on dysfunctional conflict drawn from empirical Australian and international examples in the literature.